Outliers : [compact disc, unabridged] : the story of success - Gladwell, Malcolm, 1963- (Hachette Audio, 2008)
The best-selling author of Blink identifies the qualities of successful people, posing theories about the cultural, family, and idiosyncratic factors that shape high achievers, in a resource that covers such topics as the secrets of software billionaires, why certain cultures are associated with better academic performance, and why the Beatles earned their fame.